Trajectory from brand hate to consumer decision making process (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper examines the trajectories of brand  hate leading towards the consumer decision  making process. Brand hate is an emotional  state of the consumer wherein the intensity of  consumers’ hatred and their self congruence  could determine their actions towards the  brand. 432 respondents spread across the main  cities of Gujarat, India were administered a  structured questionnaire. Principal axis factoring  method along with Regression test were applied.  Findings revealed a total accumulated variance of  59.943% for the four factors extracted using the  PAF method. Four factors identified from the  study were Simple brand hate, Negative personal  experience, Negative brand image and Poor  corporate social responsibility. The regression  analysis revealed that respondents across age  group, gender, income and occupation would  not want to be consumers again of the brand  that they hated. The second regression analysis  indicated that respondent across age and gender  had made financial sacrifice to not be consumers  of the brand they hated. Brand and marketing  managers need to closely understand and study  these consumers who hate the brand because  in today’s well connected competitive world,  negativity about brands can spread like wild  fire and damage control would be difficult if  not impossible.
Keywords: Brand hate; Negative personal experience; Negative brand image; Poor corporate social responsibility; Consumer decision making process